KAJIAN FEMINITAS PUTRI HARISBAYA DALAM WAWACAN BABAD SUMEDANG KARYA ABDUR’ROCHMAN - Anna Meirlina Sulianti; Widyasari (LPPM Universitas Terbuka, 2021)
The studi was aimed at (1) finding out citra or image of Princess Harisbaya in the Sundanese classical poetry Wawacan Babad Sumedang written by Abdur’raochman; (2) finding out a femininity study of Princess Harisbaya in the Wawacan Babad Sumedang written by Abdur’raochman. The study was a analytical description. The study used and applied qualitative methodology principles. To gain the data, literary and documentation study on Wawacan Babad Sumedang were conducted. The steps of collecting data were reading of the texts accurately, making note of relevant data, identifying and classifying the data, making data tabulation and descripton. In analyzing the structure, AJ Greimas theory was adobted. The result of the study showed that Wawacan Babad Sumedang decripting citra and habits of Princess Harisbaya and her stories.